2019
DOI: 10.1038/s41598-019-53834-7
|View full text |Cite
|
Sign up to set email alerts
|

Noisy galvanic vestibular stimulation has a greater ameliorating effect on posture in unstable subjects: a feasibility study

Abstract: Ameliorating effect of noisy galvanic vestibular stimulation (nGVS) on posture varies among subjects. In this feasibility study, we investigated the association between original postural instability and the ameliorating effect of nGVS on posture. Data were collected in a previously published study. Thirty healthy elderly were recruited. Two nGVS sessions (30 min or 3 h) were performed in a randomised order. The optimal intensity of nGVS, the most effective intensity for improving posture, was determined before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…There is so far no consensus about whether nGVS only acts during ongoing stimulation or whether it exhibits any plastic aftereffects after cessation of stimulation. In favor of the later assumption, Fujimoto et al reported in an uncontrolled study long-term effects of nGVS on postural stability that lasted up to 6 h after cessation of stimulation [ 7 ]. Later, placebo-controlled studies did not find any evidence for long-term effects of nGVS on vestibular function [ 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is so far no consensus about whether nGVS only acts during ongoing stimulation or whether it exhibits any plastic aftereffects after cessation of stimulation. In favor of the later assumption, Fujimoto et al reported in an uncontrolled study long-term effects of nGVS on postural stability that lasted up to 6 h after cessation of stimulation [ 7 ]. Later, placebo-controlled studies did not find any evidence for long-term effects of nGVS on vestibular function [ 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the clinical significance of this study, our result provides evidence for the safety of using nGVS in elderly people. While previous studies report the effectiveness of nGVS ( Fujimoto et al, 2016 , 2018 , 2019 ; Inukai et al, 2018a , b ), they provide no evidence on its impact on AP and HR variability. In future studies, the effect of nGVS on AP and HR variability in patients with cardiocirculatory disorders, such as orthostatic hypotension, arrhythmia, and heart failure, should be tested further to ensure safety.…”
Section: Discussionmentioning
confidence: 90%
“…This study is the first step toward determining whether noisy galvanic vestibular stimulation can effectively and safely enhance balance and stability in a balance retraining program. Preliminary evidence suggests that the use of subsensory noisy galvanic vestibular stimulation to enhance vestibular signals to the brain also improves stability during quiet standing and gait [ 4 , 20 , 21 , 25 , 26 ]. This study will assess the feasibility of administering a balance retraining program augmented by noisy galvanic vestibular stimulation for older adults at risk for falls.…”
Section: Discussionmentioning
confidence: 99%
“…However, this sustained effect has not been replicated consistently in other studies; Inukai et al [ 22 ] found a poststimulation effect in contrast to Nooristani et al [ 23 ] and Keywan et al [ 24 ] who did not. A secondary analysis by Fujimoto et al [ 21 ] discovered that noisy galvanic vestibular stimulation resulted in significantly greater improvements in participants who were more unsteady on initial assessment [ 25 ]. This suggests that either noisy galvanic vestibular stimulation has a greater effect on the hypofunctional vestibular system or that different noisy galvanic vestibular stimulation parameters and experimental designs play a role in these findings.…”
Section: Introductionmentioning
confidence: 99%